2014
DOI: 10.1186/1297-9716-45-19
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of immune responses induced by avian pathogenic Escherichia coli infection in turkeys and their association with resistance to homologous re-challenge

Abstract: Avian pathogenic Escherichia coli (APEC) cause severe respiratory and systemic disease in poultry yet the nature and consequences of host immune responses to infection are poorly understood. Here, we describe a turkey sub-acute respiratory challenge model and cytokine, cell-mediated and humoral responses associated with protection against homologous re-challenge. Intra-airsac inoculation of turkeys with 105 colony-forming units of APEC O78:H9 strain χ7122nalR induced transient and mild clinical signs of coliba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 36 publications
9
31
0
Order By: Relevance
“…The dietary MOS stimulates humoral immune responses against infectious bursal disease (IBDV) and Newcastle disease (NDV) vaccine viruses [29]. Regarding results of E. coli colonization, the higher colonization rates of E. coli in different organs of control infected group was in the respiratory tract, fecal swab, liver, and spleen where avian pathogenic E. coli cause severe respiratory and systemic diseases in poultry [30]. This result is in harmony with that of Manafi et al [14].…”
Section: Pathogenic E Coli Infection In Broilers Leads To Local or Ssupporting
confidence: 60%
“…The dietary MOS stimulates humoral immune responses against infectious bursal disease (IBDV) and Newcastle disease (NDV) vaccine viruses [29]. Regarding results of E. coli colonization, the higher colonization rates of E. coli in different organs of control infected group was in the respiratory tract, fecal swab, liver, and spleen where avian pathogenic E. coli cause severe respiratory and systemic diseases in poultry [30]. This result is in harmony with that of Manafi et al [14].…”
Section: Pathogenic E Coli Infection In Broilers Leads To Local or Ssupporting
confidence: 60%
“…Thus, we consider it reasonable to speculate that the loss of B cells and/or APEC-specific IgY is associated with the failure of Cy-treated vaccinated birds to control APEC. The association of antibody with protection is consistent with our studies in turkeys given the same vaccines [4] or subject to subacute primary infection [13] and suggest that work to potentiate Th2 responses and identify conserved B cell antigens of APEC may lead to more effective vaccines for control of this key avian endemic disease.…”
Section: Resultssupporting
confidence: 86%
“…Indeed, intravenous administration of hyper-immune serum [8][9][10] or egg-derived antibody [11,12] from birds given APEC vaccines to naive birds confers homologous protection. Our earlier studies have shown that antibody induced by primary infection can also be associated with clearance and resistance to APEC re-challenge [13]. To examine if B cells and thus antibody are required for vaccine-mediated protection against APEC, chemical bursectomy was induced by cyclophosphamide (Cy) treatment in chickens prior to vaccination with licensed vaccines and the degree of homologous protection and associated humoral responses assessed relative to controls.…”
Section: Introductionmentioning
confidence: 99%
“…The uninfected birds were observed to produce small quantities of T h 1, T h 2, T h 17 and T h 22 cytokines suggesting that the birds are able to recognise and mount a response to commensal bacteria in the gut which supports work by Crhanova et al (2011) who showed expression of T h 1, T h 2 and T h 17 in the caecum of noninfected chickens (Crhanova et al, 2011). These levels of expression observed could also be due to other bacteria such as Salmonella and Escherichia coli which have both been shown to induce immune responses in chickens (Matulova et al, 2013;Sadeyen et al, 2014). Expression of cytokines such as IL-1, IL-10 and IL-18 has been observed in the caecal tonsils in response to multiple Lactobacilli strains (Brisbin et al, 2010).…”
supporting
confidence: 77%